Who is Afraid of Autobiographies? On Women’s Autobiographies in the Arab World - Fadwa Tukan and Haifa Bitar - Shitrit-Sason, Sharon (Jama’a: an Interdisciplinary Journal of Middle East Studies, 2014)
The first Arab women’s Autobiographies were published in the twentieth century, as part of a global change in women’s writing. Though Women’s Literature has unique features, it is not detached from its environment’s social- cultural-political discourse. Weaving autobiographic elements into literary ‘work or disguising an autobiography as a novel can ease the author’s exposure ‘and present the conflict between the public and private-feminine spheres more credibly. In a novel with autobiographic elements or an autobiographic novel, the reader might find similarities between the author’s life and the protagonist’s, but unlike an autobiography, an autobiographic novel discloses only certain biographic pars. An author’ s life-course may have a great influence on writing, so literary work can express cultural, political and social factors. The Palestinian poet Fadwa Tukan and the Syrian author Haifa Bitar Represents two women fighting for their truth. Tukan views women’s liberation ‘as inseparable from national liberation, She thus accentuates the national aspect in her work and connects the personal feminine struggle with the national ‘one. Bitar objects to women’s repression through blunt exposure of her most difficult and secret feelings. Her divorce inspires her and she can share it with her readers by defining her work as a novel, Each writer has chosen to promote ‘a feminine agenda. Each presents a pattern of Autobiographic writing and suggests means to handle patriarchic society’s impositions.